2019
DOI: 10.3390/ijerph16193602
|View full text |Cite
|
Sign up to set email alerts
|

Local Residents’ Perceptions for Ecosystem Services: A Case Study of Fenghe River Watershed

Abstract: To make environmental management decisions more executive and targeted, it is essential for decision-making to include local residents’ perceptions and preferences for ecosystem services (ES) and biodiversity (BD). This study conducted a questionnaire survey with 386 local residents to explore social perceptions for ES and BD in the Fenghe River watershed. ES contain food from agriculture (AGR), food from livestock (LIV), fresh water (FW), air purification (AP), water purification (WP), water retention (WR), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Regarding the identification of AP as a priority, the literature emphasizes that AP is a highly valued ES in urban contexts (in terms of social importance level), given its contribution to urban quality of life [8,17,48]. Although the research on air quality recognizes the great importance of the value to be paid, few studies assign a specific amount to AP because these values are involved in multiple ES assessment contexts [8,22].…”
Section: Importance and Monetary Valuation Of Air Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the identification of AP as a priority, the literature emphasizes that AP is a highly valued ES in urban contexts (in terms of social importance level), given its contribution to urban quality of life [8,17,48]. Although the research on air quality recognizes the great importance of the value to be paid, few studies assign a specific amount to AP because these values are involved in multiple ES assessment contexts [8,22].…”
Section: Importance and Monetary Valuation Of Air Purificationmentioning
confidence: 99%
“…In general, AP has been understood as a human welfare indicator, in terms of air quality or clean air [15,16]. AP mainly embodies the production of negative tropospheric ozone, absorption of sulfur dioxide, nitrogen oxides, fluoride, particulate matter (PM10), and noise reduction [17,18]. Further, they contribute to a final benefit related to clean-air environments, by removing pollutants from the atmosphere, reducing the cost of human-led air purification, and preventing large expenditures on public health and safety [19].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies found that when people face more survival risks, their perception of the surrounding CES will be reduced [57]. People's direct experience plays an important role in shaping their perception of the surrounding CES [58]. CES can be evaluated after they are perceived.…”
Section: Future Development Managementmentioning
confidence: 99%
“…Nahuelhual et al apply willingness to pay to estimate agricultural heritage values [24]. Based on these definitions, various assessment methods for ES demand have been explored, such as the consumption method [25], the preference method [26][27][28], the contingent valuation method [29], and the matrix method [4,12]. Although these methods have promoted the progress of ES demand assessment, some obstacles still exist.…”
Section: Introductionmentioning
confidence: 99%